Ideological Aspects of Translating News Headlines from English to Persian - Khanjan, Alireza; Amouzadeh, Mohammad; Eslami Rasekh, Abbas; Tavangar, Manoochehr (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Drawing on Teun van Dijk’s socio-cognitive approach, the present paper attempts to investigate certain ideological aspects of news headlining in an English-Persian translation context. A number of parallel news headlines have been chosen for contrastive analysis, with a view to highlighting the different ideological apparatuses involved in the process of translation of news headlines. A qualitative analysis of the sample data suggests that the polarization of us and them is generally influenced by translators’/target news producers’ (dis)approval of the ideological content of the source headlines in question, and is represented through maintaining, manipulating or excluding original headlines in the target news stories. These translation strategies are typically realized through the purposeful application of linguistic expressions (both at lexical and grammatical levels) or non-linguistic elements (such as images, photos and graphic drawings).